Workshop dan Pendampingan Pemanfaatan Kecerdasan Buatan Untuk Meningkatkan Kemampuan Public Speaking Guru Yayasan Pendidikan Al-Chasanah, Jakarta - Maya Sekartaji; Wahyu Budi; Irma Rahmawati (JURNAL ComunitÃ Servizio : Jurnal Terkait Kegiatan Pengabdian kepada Masyarakat, terkhusus bidang Teknologi, Kewirausahaan dan Sosial Kemasyarakatan, 2026)
This Community Service program focuses on improving the English public speaking skills of teachers at Yayasan Pendidikan Al-Chasanah in Jakarta through a workshop incorporating Artificial Intelligence (AI) technology. Conducted on December 13, 2025, the workshop involved 16 teachers from junior and senior high school levels. The training utilized a Micro-Learning and Immediate Feedback approach, consisting of five stages: a pre-training video, theory introduction, SpeechAce technology demonstration, performance practice, and self-assessment with SpeechAce. The PkM team gathered data from video recordings, AI scores from SpeechAce, and a CEFR-based speaking analysis. Results showed that all 16 participants completed performance recordings, overcoming psychological barriers to public speaking in English. Video analysis indicated a range of abilities from A1-A2 to B2-C1, with most participants at the B1 level. This program highlights the effectiveness of AI technology as a self-training tool for teachers looking to enhance their English communication skills. Keywords: artificial intelligence; public speaking, SpeechAce